Monitoring tools as energy saving enablers in social housing context - Jacopo Gaspari; Lia Marchi; Carlotta Oberosler; Ernesto Antonini (Agathón)
The improvement of the digital infrastructure envisaged by the National Recovery and Resilience Plan (PNRR) promises new opportunities for reducing energy consumption based on user behaviour for the residential sector. Smart tools for energy monitoring would make it possible to improve indoor comfort, limit household expenses and reduce their environmental impact, with particularly appreciable effects in social housing. However, the diffusion of these technologies, which are already available on the market, largely depends on the ability of users to actively interact with them and on the understanding of their advantages. The study investigates the interaction of users with the typical system and equipment of social housing, comparing the opinion of the inhabitants with instrumental monitoring on a pilot case in Bologna, in order to define the characteristics of an integrative tool to inform the user and suggest good energy use practices.